(untitled) (Research, Society and Development, 2026)
Graphene is a two-dimensional nanomaterial consisting of a single layer of carbon atoms arranged in a hexagonal lattice, whose properties were theoretically described by Wallace in 1946. Currently, it stands out for its high mechanical strength, high electrical and thermal conductivity, and large specific surface area, characteristics that make it promising for various technological applications. However, the production and characterization of graphene still represent challenges, since structural defects, impurities, and variations in the synthesis method may compromise its properties. In this context, this study aimed to characterize a commercial graphene using structural, morphological, and chemical techniques. Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were employed. The results indicated the predominance of a well-organized structure, with residual presence of oxygen-containing groups, partial stacking of the sheets, and a moderate number of layers. Raman analysis evidenced a low density of defects and good organization of the carbon network, while the micrographs revealed thin, lamellar, and partially overlapped sheets. Thus, proper characterization of graphene is convenient and necessary to understand its properties and, consequently, to efficiently direct its application in different systems and technologies.